Cutaneous composite lymphoma of mycosis fungoides and Hodgkin lymphoma: Response to sequential therapy. (28th May 2020) - Chen, Yudi; Nong, Lin; Li, Xin; Wang, Yang
Abstract: Composite lymphoma is defined as two or more morphologically and immunophenotypically distinct lymphoma clones that occur in the same tissue site. The occurrence of cutaneous composite lymphoma (CCL) is extremely rare. Here we report a unique case of CCL consisting of Hodgkin lymphoma (HL) and mycosis fungoides (MF). Our patient presented with longstanding erythematous plaques on the skin and later developed axillary lymph node enlargement. Histopathologically, the skin lesions were characterized by a dense dermal lymphocytic infiltrate with prominent epidermotropism of pleomorphic T‐cells, consistent with typical MF. Nonetheless, scattered large atypical cells resembling Reed‐Sternberg (R‐S) cells were interspersed among these atypical T‐cells in the deep dermis. Immunophenotyping suggested a HL origin of these R‐S cells. Monoclonality of T‐cell receptor beta gene was detected in the skin, monoclonal immunoglobulin heavy chain gene rearrangement was identified in these R‐S cells microdissected from the deep dermis, confirming the origin from HL. The lymph node biopsy showed nodular sclerosis classic Hodgkin lymphoma. Therefore, CCL of HL and MF, with lymph node HL was diagnosed. The lesions of this patient responded to a sequential treatment to HL and MF. Being aware of this rare CCL facilitates correct diagnosis and proper clinical management.